Preparation of site specific transmission electron microscopy plan-view specimens using a focused ion beam system - Langford, R; Huang, Y; Lozano-Perez, S; Titchmarsh, J (2001)
A focused ion beam system was used to prepare site specific transmission electron microscopy plan view specimens. A new technique was used for this purpose. It consisted of milling a wedge shaped piece of material, lifting it out using needle and micromanipulator, and orientating it on the substrate with the original surface vertical. Based on the lift-out technique for the preparation of a cross-section specimen, the plane-view specimen was then milled from this piece of material.